ANALISIS PERENCANAAN DAN PENGENDALIAN PERSEDIAAN BAHAN BAKAR MINYAK SOLAR INDUSTRI PT.WILLY DWI PERKASA - Indah Andestya; Aried Sumekar (Worksheet : Jurnal Akuntansi, 2022)
The purpose of this research is to find out and analyze the application of industrial diesel fuel inventory planning at PT. Willy Dwi Perkasa, to identify and analyze the application of industrial diesel fuel inventory control and to identify and analyze the application of industrial diesel fuel inventory planning and control at PT. Willy Dwi Perkasa. The data collection technique used in this research is by using interviews, observation and documentation studies, while the data analysis technique in this study is a qualitative descriptive method. The conclusions in this study are that the planning carried out for the smooth distribution of industrial diesel fuel in the market is by setting goals, developing commitments to achieve goals, developing effective plans, tracking progress and maintaining flexibility and planning for industrial diesel fuel inventories in PT. Willy Dwi Perkasa.